Oxidation behavior of nano-structured (Al2O3+Y2O3)/AlY coating on γ-TiAl upon exposure to 1200 °C. Issue 4 (March 2019) - Xu, Yi; Shi, Pengfei; Cui, Shiyu; Li, Yanhui; Xu, Aoni; Wang, Jiaming; Yao, Zhengjun; Zhou, Xuefeng; Yuan, Ting; Liu, Wanhui; Chen, Jiayuan
Abstract: Developing γ-TiAl intermetallic alloys as candidate materials for manufacturing components of aircraft gas turbines has been limited because of their poor oxidation resistance at high temperature. In this study, a nano-structured (Al2 O3 +Y2 O3 )/AlY coating was deposited on a γ-TiAl alloy by sputtering, to improve its oxidation resistance. To evaluate this coating under real-life critical operating conditions in aircraft engines, the isothermal oxidation exposure at an elevated temperature of 1200 °C was carried out. The analysis results indicated that Al and Y diffused through the grain boundary to synthesize or grow oxides outward, toward the testing atmosphere during the oxidation tests. During this process, oxygen was somewhat prevented from penetrating the coating because of the strong oxytropism of the coating surface to form Al and Y oxides. The coating exhibited a nanosized Al and Y oxides surface morphology after 100 h of oxidation. Weight change kinetics revealed that the weight gain of the coating was 7.49 mg/cm 2, while that of the substrate fluctuated because of oxide scale spallation. The nano-structured (Al2 O3 +Y2 O3 )/AlY coating improved the oxidation resistance of the γ-TiAl alloy at elevated temperature.